Prestige of products and code-switching in retail encounters - Ting, Su Hie; Then, David Chen On; Ong, Oliver Guan Bee (Routledge, 2020)
The study examined code-switching in retail encounters involving sales personnel of cars, credit cards, beauty products, and food products with a Chinese customer. Altogether 27 retail encounters were audio-taped and transcribed. Analysis of the 14,944-word corpus was conducted using Gumperz’s [(1982). Discourse strategies. Cambridge: Cambridge University Press] model of conversational code-switching. The results showed that English and Hokkien were the main base languages for retail encounters involving a Chinese customer who could not speak Mandarin. English marked prestige of products, notably car and credit card, whereas beauty and food products were promoted in Hokkien or Malay. The main code-switching functions were referential functions and interjections (41.57% and 39.36% of 907 instances, respectively). The most common referential function was product description. Reiteration accounted for 9.92% of the code-switching instances but message qualification, personalisation versus objectivisation, address specification, and situational codeswitching were minimally present. Product type did not influence frequency of code-switching for interjection but it affected referential functions and reiteration. Referential function was the least frequent in credit card retail encounters and reiteration was the most frequent in food retail encounters. The findings on the high frequency of reiterations and the minimal use of codeswitching for personalisation showed that clarity is more important than solidarity in retail encounters.